Comparison of Visual and Tomographic Outcomes of Epithelium-On and Epithelium-Off Accelerated Corneal Crosslinking: A Longitudinal Study. Issue 5 (May 2021) - Niyazmand, Hamed; McKelvie, James; Li, Ye; McLintock, Cameron
Abstract : Purpose: To compare the visual and tomographic outcomes of epithelium-on and epithelium-off corneal collagen crosslinking (CXL) in an accelerated protocol in eyes with progressive keratoconus. Methods: Sixty-one patients with progressive keratoconus (female patients, n = 30; male patients, n = 31) aged 17 and 48 years (mean age: 25.8 ± 6.2 yrs) were included in this study. Patients underwent either epithelium-off (n = 27) or epithelium-on (n = 34) CXL using an accelerated protocol. Patients with at least 12 months of follow-up were included in the study. Visual and tomographic data from 3, 6, and 12 months after surgery were analyzed. Results: There were no differences between the visual and tomographic characteristics of the epithelium-on and epithelium-off groups at baseline ( P > 0.05). No significant changes in uncorrected and best spectacles-corrected visual acuity were found at any stage during the first 12 months within either group or between the groups (all P > 0.05). There were no changes in thickness and keratometric parameters at any stage during the first 12 months within either group, or between groups ( P > 0.05) except for a transient significant thinning of the central cornea in all groups in the first 3 months which recovered by 6 months. There was no significant difference between groups regarding the number of eyes with progression in the 12 months after treatment ( P > 0.05). Conclusions: Epithelium-on and epithelium-off CXL in an accelerated protocol provide comparable visual and tomographic outcomes after 1 year in eyes with progressive keratoconus.